The Commission's internal conditions for social re-regulation: Market efficiency and wider social goals in setting the rules for financial services in Europe - Miriam Hartlapp; Christian Rauh (European Journal of Government and Economics (EJGE), 2013)
The European Union is often considered as a prime example of a liberal regulatory state. We argue, however, that being limited to the regulatory policy does not prevent the European Commission from pursuing political aims going beyond market efficiency. We draw up two ideal-type perspectives of market regulation - being either efficiency or equality enhancing - that differ systematically in terms of rationale, degree of intervention, patterns of stakeholder access and conflict within the regulator. We trace these aspects in three financial services initiatives on the registration and supervision of reinsurers, equal treatment in financial services and the regulation of consumer credit. Our analyses suggest that there is scope for equality-enhancing re-regulation when proactive agents proceed decidedly on the basis of social-treaty concerns and frame regulatory beneficiaries as market participants as well as when they seek the redistribution of rights instead of resources.
Keywords: 330; European Union; regulation; financial services; equality enhancement